Developing a Prototype of Mobile Dental Information System in Indonesia - Santoso, Leo Willyanto; Setiawan, Alexander; Gunawan, Samuel (Jurnal Buana Informatika, 2012)
Abstact. With the rapid development of wireless technology, mobile devices applications and services have become more convenient. One area that can be supported by this technology is the field of health, particularly in the dental information system. Processing the patient data is one of the many factors that have an important role in hospital industry. The manual processing of patient data in dental clinic 'X' Yogyakarta, Indonesia is inefficient and ineffective. It can't guarantee the accuracy of the calculation, recapitulations, and reporting system. The rapid development of information technology makes it possible to develop a dental information system, which gives accurate reports on the status of the patients in real time for the purpose of improving patient’s safety and quality of services. In this research, the application is developed with Java programming language and mySQL database. The testing results of the application have shown that the program can be operated easily, has a clear work flow, supports various facilities that help users, and is able to become valuable inputs for dental clinic management in the decision making process. Based on the questionnaire results, 80% respondents reported that the program met the requirements and was easy to use.Keywords: mobile technology, dental information system, registration, report Abstrak.Perkembangan teknologi nirkabel yang sangat pesat telah memicu aplikasi dan layanan seluler menjadi lebih nyaman. Salah satu bidang yang dapat didukung oleh teknologi ini adalah bidang kesehatan, terutama dalam sistem informasi klinik gigi. Pengolahan data pasien merupakan salah satu faktor yang memiliki peran penting dalam pengelolaan industri kesehatan. Saat ini, proses manual pengolahan data pasien di klinik gigi 'x' Yogyakarta tidak efisien dan tidak efektif. Hal ini tidak dapat menjamin keakuratan perhitungan, rekapitulasi, dan sistem pelaporan. Pesatnya perkembangan teknologi informasi memungkinkan untuk mengembangkan sistem informasi gigi, yang memberikan laporan yang akurat tentang status pasien secara real time untuk tujuan meningkatkan keselamatan pasien dan mutu layanan. Dalam penelitian ini, aplikasi dikembangkan dengan bahasa pemrograman Java dan database mySQL. Hasil pengujian aplikasi telah menunjukkan bahwa program ini dapat dioperasikan dengan mudah, memiliki alur kerja yang jelas, mendukung berbagai fasilitas yang membantu pengguna, dan mampu menjadi masukan yang berharga untuk manajemen klinik gigi untuk membuat keputusan. Berdasarkan hasil survey, 80% responden berkata bahwa program sudah memenuhi kebutuhan dan mudah untuk digunakan.Kata kunci: teknologi bergerak, sistem informasi dokter gigi, registrasi, laporan